Legal Certainty for Unregistered Marriages in Indonesia: A Study of the Isbat Nikah Decision of the Palangkaraya Religious Court No. 339/Pdt.G/2024/PA.Plk - Maharani, Syaima Desinta; Hasanah, Uswatun; Amin, Fadli; Mayada, Aulia (Institut Agama Islam Negeri (IAIN) Curup, 2025)
This study was conducted in response to the prevalence of unregistered marriages in Indonesia, which have serious implications for the rights of husbands, wives, and children, and hinder the population administration process. This article aims to analyze, from a legal-normative perspective, the practice of legalizing unregistered marriages through the mechanism of marriage validation in the Religious Court of Palangkaraya City. The main focus of this research is Decision Number 339/Pdt.G/2024/PA.Plk, with the aim of exploring in greater depth the legal considerations used by the judge in granting the marriage validation request. The research method used is normative legal research with a descriptive qualitative case study approach. The primary data in this study is Decision Number 339/Pdt.G/2024/PA.Plk, supplemented by interviews with the judge. Meanwhile, the secondary data consists of scientific literature related to the research theme. The data was collected through document studies and semi-structured interviews with the judge. The results of the study show that the marriage validation petition in decision No. 339/Pdt.G/2024/PA.Plk was driven by the need to obtain legal certainty regarding the status of the marriage, provide legal protection for the rights of the wife and children, and facilitate the fulfillment of administrative requirements such as processing BPJS Ketenagakerjaan (Social Security Administration Agency for Employment) claims and other population documents. The judge granted the marriage validation petition based on the fulfillment of the requirements and pillars of marriage according to Islamic law, the absence of marriage barriers, and convincing evidence. In conclusion, marriage validation at the Palangkaraya Religious Court not only serves as a formal legalization of unregistered marriages, but also as a strategic means to achieve justice and provide legal protection for people whose marriages are not officially registered, while affirming the state's existence in protecting the rights of its citizens, thereby ensuring legal certainty.